DETERMINAN INFORMASI AKUNTANSI USAHA KECIL DAN MENENGAH DI BOYOLALI - Melinda Selvia Ramadhani; Pardi Pardi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
The purpose of this study is to determine statistically the influence of accounting information on company culture variables, business experience and business scale in Small and Medium Enterprises in Boyolali. The method used is a quantitative approach by utilizing primary data obtained by providing a number of written questionnaire sheets intended for SMEs in Boyolali regency which is then directly processed through utilizing IBM SPSS Statistics 25 software. The results of this research activity indicate that partially the variables of company culture and business experience have no significant effect on accounting information. Therefore, business scale variables have a significant effect on accounting information. While the results of simultaneous testing indicate if the independent variable has a significant effect on the dependent variable.